2019
DOI: 10.1186/s12882-019-1660-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of acute kidney injury in intensive care units in Beijing: the multi-center BAKIT study

Abstract: BackgroundAcute kidney injury (AKI) commonly occurs in intensive care units (ICUs), leading to adverse clinical outcomes and increasing costs. However, there are limited epidemiological data of AKI in the critically ill in Beijing, China.MethodsIn this prospective cohort study in 30 ICUs, we screened the patients up to 10 days after ICU admission. Characteristics and outcomes were compared between AKI and non-AKI, renal replacement therapy (RRT) and non-RRT patients. Nomograms of logistic regression and Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 44 publications
4
47
4
5
Order By: Relevance
“…In the current study, the incidence of AKI (39.0%) was less than that reported in a large Chinese cohort study [14] conducted in 30 ICUs where the incidence of AKI was 51.0%. This variation can be attributed to the characteristics differences between the two populations and the criteria used for the classification of AKI.…”
Section: Comparison Between the Findings Of The Current Study And Othcontrasting
confidence: 77%
See 1 more Smart Citation
“…In the current study, the incidence of AKI (39.0%) was less than that reported in a large Chinese cohort study [14] conducted in 30 ICUs where the incidence of AKI was 51.0%. This variation can be attributed to the characteristics differences between the two populations and the criteria used for the classification of AKI.…”
Section: Comparison Between the Findings Of The Current Study And Othcontrasting
confidence: 77%
“…The Chinese study has excluded nearly 6000 subjects (3107 participants were included in the final analysis among the 9049 subjects admitted to the participating ICUs during the study period) which might have affected the reported mortality. The incidence of AKI has included stage one (23.1%), stage 2 (11.8%), and stage 3 (15.7%) [14]. However, in our current study, the severity grading of AKI was mainly staged 1 (45.5%) and stage 2 (54.5%).…”
Section: Comparison Between the Findings Of The Current Study And Othcontrasting
confidence: 65%
“…A recent large, multicenter epidemiological study (BAKIT [Beijing Acute Kidney Injury Trial] study) conducted in the ICU showed that KDIGO stage 3 AKI accounted for 16% of critically ill patients ( 7 ). This incidence was 15% in a secondary analysis of the LUNG SAFE (Large Observational Study to Understand the Global Impact of Severe Acute Respiratory Failure) study ( 8 ).…”
mentioning
confidence: 99%
“…The incidence of AKI in these circumstances, predominantly in situations with presentation of septic shock, may be as high as 47.5% and the overall mortality in critically ill patients with AKI may be more than 60% [ 3 ]. According to recent results of a multicenter Chinese study of patients hospitalized in ICUs, the incidence of AKI was 51%, with the majority occurring on the 4th day after admission [ 4 ]. A number of factors can contribute to AKI and progression to renal failure, including cardiovascular and hepatic disorders, malignancies, hypovolemia, intoxication, drug nephrotoxicity, anemia and surgical and vascular interventions.…”
Section: Epidemiology Of Acute Kidney Injurymentioning
confidence: 99%